“Proud, brave, and tough”: women in the Canadian combat arms - Hendel, Emalie; MacEachern, Kate Hill; Haxhiu, Alma; Waruszynski, Barbara T. (Frontiers in Sociology, 2024)
Canada’s defence policy, Strong, Secure, Engaged, emphasizes the importance of leveraging Canada’s diversity to strengthen the Canadian Armed Forces. Currently, women in the Canadian military are underrepresented across most elements and occupations, especially in the combat arms occupations, including among officers and non-commissioned personnel in combat units such as infantry, armored corps, artillery, and combat engineering. Research suggests that the benefits associated with the inclusion of women in combat arms occupations include an increase in collective intelligence, operational effectiveness, task cohesion, and diversity. This article explores the gender gap in the Canadian combat arms by examining the findings from two recent qualitative research studies on the perceptions of women in the Regular Force and Primary Reserve. The authors analyze female military personnel’s perceptions of women serving in the combat arms, and the ways to increase their inclusion in the military. The key findings reveal the following themes on women’s perceptions of servicewomen in the combat arms: great job for those who want it; challenging environment (e.g., working within a masculinized culture, necessary toughness, tokenism and the “pink list,” being treated differently, and family loyalty); unique challenges faced by women in combat roles; combat takes a toll on women’s mental and physical health; and benefits of women’s participation in multinational operations. The discussion highlights the need to increase diversity, equity, and inclusion, promote a culture change that fosters greater inclusion of women in the combat arms, and increase operational effectiveness through training and policies.